Supposed techniques to overcome institute corruption that result from bad use of database management system - A.younis, Hussain; Salem Abbas, Ahmed; M. Hayder, Israa (International Journal of Engineering and Technology, 2018)
The nations of the world today are measured by their scientific potentials in the extent to which they use the modern technologies and possibilities in the information and communication sector to constantly progress, that reflected as electronic government, communication networks, computer control, etc. As these possibilities and advantages, it is difficult to say that there is negative on Data base management system present or future because of the urgent need in the present day. The most important difficulties in this area may be the problem of misuse of these techniques. This research raises one of these problems, which are part of the misuse, lead in turn to administrative corruption is difficult to control and research sets the mechanism for the design of database programs that can reduce the bad use of it as one of the most important pillars of e-government. This mechanism makes the monitoring system able to identify and retrieve data that has been illegally manipulated for certain purposes and benefits or through the misuse of inaccurate work in order to integrate the digital system that was originally designed for human service. Â Â Â